Thermal Spray Coatings: Materials, Techniques & Applications - Kumar, Santosh; Khanna, Virat (Bentham Science Publishers, 2024)
This comprehensive book explores the techniques, materials, and real-world applications of thermal spray coatings across various industries, including power generation, aerospace, medical, and automotive sectors. Readers will learn about the basic science and engineering aspects of thermal spray technology, its historical developments, and the diverse range of materials used, from metallic to ceramic materials, and nano-crystallization materials. Distinct thermal spray techniques are explained (flame spray, detonation-gun spray, high-velocity oxy-fuel spray, electric arc spray, plasma spray and cold spray). Chapters on advanced topics also give an understanding of crucial material properties such as high temperature corrosion, oxidation, erosion or wear resistance, and biocompatibility. Key features - Contributions from materials science experts with references for each topic - Gives a comprehensive overview of materials and distinct spray techniques used in thermal coatings - Dedicated chapters for applications of thermal coatings in different industries - Covers recent trends and new advances such as surface modification techniques to improve functionality and performance This book is intended as a resource for an in-depth understanding of the fundamentals and applications of thermal spray coatings for students, professionals and researchers in materials science and chemical engineering disciplines.